Pendekatan Tele-Rehabilitasi Pada Pasien Stroke: Literature Review - Kasrin, Rinawati (REAL in Nursing Journal, 2021)
Abstract: Stroke is a condition where blood supply to the brain is disrupted, resulting in lack of oxygen, brain damage and loss of function. Post-stroke is the most difficult period for patients, they will experience disability and the inability to carry out activities as usual and they will have difficulty in self-care. To sustain life rehabilitation is an important component of post-stroke management. The rehabilitation therapy is to improve motor function, cognitive, emotional, psychological and social well-being. In reality there are many barriers for stroke survivors to access rehabilitation care face-to-face such as time restrictions, limited resources, geographical isolation, adherence to rehabilitation, and lack of awareness. One way to overcome access barriers is through technological innovation with tele-rehabilitation. The purpose of writing this literature review is to analyze the implementation of tele-rehabilitation in stroke patients. The data sources used are from databases such as PubMed, Proquest and Google Scholars. There were 21 relevant articles and 5 of them became the material for analysis in this study. The results of the review found that tele-rehabilitation could be a suitable choice as an alternative for post-stroke rehabilitation care for patients. This has potential implications for patients, especially in remote or underserved areas.Keywords:approach, tele-rehabilitation, stroke patients